2016
DOI: 10.1590/1678-4499.439
|View full text |Cite
|
Sign up to set email alerts
|

Substrates and containers for the development of Brassica pekinensis L. seedlings

Abstract: ABSTRACT:The aim of this study was to evaluate the development of Chinguensai (Brassica pekinensis L.) seedlings, under different formulations of substrates and sizes of containers, in Fortaleza, Ceará.For this, two studies were conducted in factorial design with randomized blocks and four replicates. The first study was conducted in a factorial (31, 18 and 11 cm³) and four evaluation dates (22, 27, 34 and 41 DAS). The fresh and dry weight of the shoot and root systems was evaluated. Both studies showed no int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
0
0
2
Order By: Relevance
“…In general, the responses observed for the characters evaluated show similar responses, being the container of larger volume (100 cm 3 ) and the increase in the doses of CRF, those that allowed obtaining plants with better performance. These results are similar to others obtained by researchers who focused their studies on the selection of containers and substrates for seedling production (Seabra Júnior;Gadun;Cardoso, 2004;Danner et al, 2007;Echer et al, 2007;Guimarães et al, 2012;Lemos Neto et al, 2016). In general, containers with larger volume, besides providing more space for root development, because they have a greater amount of substrate in their cells, end up providing the plants with a higher concentration of essential nutrients for their growth and development (Klein et al, 2012;Guimarães et al, 2012;Lemos Neto et al, 2016).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In general, the responses observed for the characters evaluated show similar responses, being the container of larger volume (100 cm 3 ) and the increase in the doses of CRF, those that allowed obtaining plants with better performance. These results are similar to others obtained by researchers who focused their studies on the selection of containers and substrates for seedling production (Seabra Júnior;Gadun;Cardoso, 2004;Danner et al, 2007;Echer et al, 2007;Guimarães et al, 2012;Lemos Neto et al, 2016). In general, containers with larger volume, besides providing more space for root development, because they have a greater amount of substrate in their cells, end up providing the plants with a higher concentration of essential nutrients for their growth and development (Klein et al, 2012;Guimarães et al, 2012;Lemos Neto et al, 2016).…”
Section: Resultssupporting
confidence: 87%
“…In relation to the containers, the larger volume made possible to obtain plants with a greater number of leaves, leaf area, plant height and accumulation of fresh mass of the shoot (Figure 2). Other research has also shown a tendency for greater growth in plants grown in larger containers, for example, greater number of leaves in Solanum sessiliflorum and Solanum paniculatum (Guimarães et al, 2012); greater leaf area in melon (Maynard: Vavrina; Scott, 1996), watermelon Latimer, 1995), okra (Modolo, 1998) and lettuce (Silva et al, 2000); greater plant height of beet (Echer, et al, 2007), eggplant (Costa et al, 2011), tomato (Oliveira et al, 2011), Brassica pekinensis L. (Lemos Neto et al, 2016) and cabbage (Nava;Marreiros, 2021) and higher values of fresh mass of the shoot in lettuce (Marques et al, 2003) and cauliflower (Godoy;Cardoso, 2005). According to the researchers, the greater availability of water and nutrients for the plants submitted in larger containers contributed to a greater development of the plants.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…O melhor desempenho das mudas produzidas em recipientes de maior volume (162 células), também foi relatado por outros pesquisadores para diferentes espécies (Costa et al, 2011;Guimarães et al, 2012;Miqueloni et al, 2013;Lemos Neto et al, 2016). Segundo os pesquisadores, tais resultados podem ser explicados devido à maior quantidade de substrato disponibilizado para as plântulas em bandejas com maior volume de substrato (menor número de células).…”
Section: Resultsunclassified
“…Atualmente, são encontrados diferentes recipientes para a produção de mudas, todos com diferentes características como: número de células, profundidade, volume e formato (Guimarães & Feitosa, 2015). No entanto, das características citadas, o volume disponível no recipiente é a que mais impacta no crescimento e desenvolvimento inicial das mudas, como já demonstrado em diferentes trabalhos realizados (Costa et al, 2012;Guimarães et al, 2012;Lemos Neto et al, 2016;Mello et al, 2016).…”
Section: Introductionunclassified